Sea star Henricia spiculifera (Clark, 1901) in the northwestern Pacific: one species or three? - Chichvarkhin, Anton (PeerJ, 2017)
Three species of the sea stars are reported from the waters of the northwestern Pacific. These species were referred by earlier authors as Henricia spiculifera or H. leviuscula spiculifera. Two of them, H. lineata and H. uluudax, were recently described from the Aleutian Islands. These species are reported for the first time from the western Pacific (southeastern Kamchatka shore, Commander Islands, and the northern Kurile Islands). The third species, H. olga sp. n. is herein described from the northern Sea of Japan. It is very likely that similar sea stars recorded in Yellow Sea and the southern Kurile Islands belong to H. olga sp. n. These three species are a part of a phylogenetic clade within the subgenus Setihenricia, which also includes H. sanguinolenta, H. multispina, and several undescribed species occurring in the northeastern Pacific.